Genesis of the Russian agro-industrial complex: historical and legal aspect - Kichalyuk Olga; Morozova Oksana (E3S Web of Conferences, 2021)
The article examines the genesis of the agro-industrial complex of Russia in the historical and legal aspect. The authors analyze the stages of the development process of the agrarian sector of the Russian economy, covering the period from 1918 to 2000, noting both positive and negative events that took place locally in the state policy of the country for the specified period. The authors emphasize that at the turn of the 1980s and 1990s, the socialist system of regulation of the economic mechanism of the agro-industrial complex completely outlived its usefulness, which contributed to the adoption of political decisions that marked the beginning of the modern stage of development. agrarian reform in Russia. Today, in a difficult foreign policy situation, the preconditions are being created within the country to stimulate and develop the domestic agro-industrial complex, which is the basis of the country’s food security.